Translation and Openness - Sandrini, Peter; García González, Marta (innsbruck university press, 2015)
"Thinking about openness and implementing openness in our attitudes and actions have considerable bearing on our conception of ourselves as translators or researchers. Openness indeed questions the very role of translated texts, multilingual translation resources, the ethics of translators, their professional behavior, the self-conception of academics and researchers, as well as the role and availability of research results in society. It therefore constitutes one of the most stimulating challenges that the world of professional translation and translation studies have yet faced. The contributions to this volume review some of these topics in three thematic sections: the first and most substantial part deals with the concept of openness in ICT (open data, open tools, open computer systems, and quality evaluation of open software), the middle part is concerned with translators training and the use of open software, and the last part discusses openness in academia on the basis of the concepts of a Scientist 2.0 and Digital Scholarship. An exhaustive list of references covering the topic is given as an appendix, as well as a keyword index."